Super Strong and Multi-Reusable Supramolecular Epoxy Hot Melt Adhesives - Sun, Peng; Li, Yuquan; Qin, Bo; Xu, Jiang-Fei; Zhang, Xi (ACS materials letters, 2021)
Hot melt adhesives are widely applied owing to their solvent-free nature. Developing robust and multi-reusable hot melt adhesives without harsh bonding conditions remains a great challenge. Herein, we develop a novel strategy of incorporating flexible side chains into the network of highly noncovalently cross-linked hot melt adhesives to construct super strong and multi-reusable supramolecular epoxy hot melt adhesives (SEA). The SEA was prepared via polycondensation of diglycidyl ether of bisphenol A with O-(2-ureido-4[1H]-pyrimidinone)-O′-(2-aminopropyl)polypropylene glycol (the noncovalent cross-linker) and O-(2-aminopropyl)-O′-(2-methoxyethyl)polypropylene glycol (the flexible side chain). Impressively, the prepared SEA was endowed with a super high adhesion strength of 10.2 MPa, which is the highest adhesion strength in bonding stainless steel among hot melt adhesives constructed by dynamic bonds to the best of our knowledge. It also featured excellent multiple reusability with more than 80% of the original adhesion strength remained even after reuse for six times. Meanwhile, the SEA displayed an outstanding ability to bond diverse substrates tightly under considerably moderate bonding conditions (80 °C for 5 min). It is highly anticipated that this work will open a new avenue of designing hot melt adhesives with the high adhesion strength and excellent multiple reusability.